Investigating the Impact of the Learning Management System Usage on the Students? Performance for Object-Oriented Programming Course - Ibrahim Z.; Jamaluddin J.E.; Anuar A. (Springer Science and Business Media Deutschland GmbH, 2025)
Learning Management Systems (LMS) are pivotal in contemporary education, enhancing curriculum delivery and course management. Their multifaceted tools and features allow educators to craft a dynamic and interactive learning experience tailored to meet diverse student needs and preferences. Furthermore, the analytical capabilities of an LMS provide invaluable insights from student engagement and usage data, potentially revolutionizing teaching and learning processes. This research delved into the LMS usage patterns for a specific course, seeking to discern its influence on students? course performance. Engagement data related to various course activities and resources within the LMS were extracted and analyzed. Descriptive statistics were employed to interpret the findings. Notably, a positive correlation emerged between high LMS usage and superior student performance. However, this correlation was absent in the low and medium usage groups. These results underscore the importance of adeptly integrating LMS into course delivery and the value of harnessing LMS analytics data. ? The Author(s).